Proyecto de factibilidad para la creación de una microempresa de producción y comercialización de envases plásticos para líquidos (toma todos) en formas de dibujos animados para el cantón mejía, de la provincia de pichincha - Loaiza Guzmán, Juan Carlos (2016)
For this thesis has been raised as a general objective to develop a feasibility project for the creation of a microenterprise Production and marketing of plastic containers for liquids (Take all) in cartoon shapes for Mej, in the province of Pichincha, which it has been raised using different techniques and applying different research methods that allow for, as the scientific method consenting to establish relationships between facts and state laws that explain the phenomena involved in the research problem, deductive method, based on the size of the sample, general and actual data of the population at the local level potential demand, real, effective and unsatisfied demand, determined Inductive Method was used to make an analysis of the information collected of the surveys, the synthetic analytical method which allowed, apply the administrative sciences and through which the generalizing laws of the company's production and marketing of plastic containers (take all) for Mej were determined, the statistical method allowed to measure the results of the surveys, and the largest percentage of which was set allowed to determine the question of the feasibility of creating a production company and marketing of plastic containers (take all). the survey technique applied to the study population covering families Mej of the Province of Pichincha with a sample of 393 families and businesses who market plastic containers (Take all) in Canton was also used with a sample of 141negocios. In this study of 32,766 effective demand takes all, for the first year of establishment of the company, value representing 97.86% acceptance by families who buy plastic containers (take all) was established, and a average annual purchase per family of 2 takes all. The offer was also identified in a significant number of establishments that sell canton Mejia plastic containers (take all), earning an average annual sales of 257 takes all. Resulting in an unmet demand for 32,509 plastic containers (take all), which shows that there is little demand for the product on the market, but there is not enough supply to cover it. As for the technical study the size of the project, with an installed capacity of 100% of 162,240 plastic containers (take all), and a capacity utilization for the first year of production of 50% of 27,040 plastic containers it was determined (take all) . the location and physical distribution of the company was established; as project engineering corresponding to the description of the production process of plastic containers (take all) and resources needed for their manufacture. As it regards the organizational study, a limited liability company, whose corporate name is settled: "Super-Take-All Cia. Ltda. "; it will have a useful life of 10 years. For the company to efficiently fulfill its activities, an administrative structure that allows appropriate use of resources was made; through the development of hierarchical levels you as well as structural, positional and functional organization charts; in addition to the operating manuals for each position. As a result of previous studies, economic study of the company was conducted, determining budgets of fixed assets, deferred assets and current assets; They are giving them a total of necessary investment of $ 64.939,13, value that will be funded with partners' capital and credit granted by the National Development Bank. the total cost of production projected for the ten-year life of the company, being the first year of $ 80,881.71, with which a unit cost of $ 2.99 production is obtained, which value is assigned is also displayed a profit margin of 54%, resulting in a retail price of $ 4.61 sales revenue for the first year will be $ 124,557.83, with a net profit (profit and loss) $ 26.061,54 and assuming the obligations of the utility workers, income tax and legal reserve. Breakeven for costs was classified into fixed and variable, resulting in the first year an installed capacity of 49.62%, and sales of $ 61.808,39, which at this point the company breaks even ; but if these values are lower than the equilibrium point obtained, the company has losses and if they are older have utilities. Finally, the financial evaluation of the project was carried out, based on the cash flow obtained and setting the different indicators that comprise it. On the Net Present Value (NPV) of $ 32.796,98 an outcome which is positive and greater than 1 was obtained, interpreting that the project is feasible because it creates value over the years. In the Internal Rate of Return (IRR) A 20.29%, which shows that the project should be accepted as the IRR is greater than the cost of capital is 11.80% was obtained. In the Capital Recovery Period (PRC), the project investment is recovered in 3 years, 2 months and 19 days. As for the cost / benefit ratio (RBC), for every $ 1 the company to invest, you will get $ 0.55 of profit. With regard to sensitivity analysis, the project is accepted as it is not financially sensitive to the increased costs up to 31.96%, as it is not sensitive to the decrease in revenues up to 20.76%. With all the information gathered and after the results of each of the studies information, it is concluded that the proposed project is profitable for that reason its realization is feasible